Analysis of Internal and External Inhibiting Factors on Maneuverability on the Kmp. Trisakti Adinda Ship - Putu Vaniesa Adnyani; Capt. Firdaus Sitepu; Dian Junita Arisusanty; I'ie Suwondo (International Journal of Science and Environment (IJSE), 2026)
The Bali Strait is a busy shipping lane with heavy traffic, where external factors such as strong winds and currents often hinder the maneuverability of Ro-Ro vessels like the KMP Trisakti Adinda, interacting with internal factors such as hull fouling. This study aims to identify the internal and external factors hindering maneuverability as well as mitigation efforts. Using a descriptive qualitative approach, the population consisted of the entire crew (22–28 people) on the Ketapang–Gilimanuk route, with a purposive sample of five key informants (Captain, First Mate, Engineer). Instruments included semi-structured interviews, observation, and documentation; analysis followed the Miles–Huberman method (reduction, display, verification). Results indicated that wind (20–30 knots), drift currents, low visibility (<0.5 miles), flat-bottomed hulls vulnerable to side forces, and fouling increased resistance by 5–10%. Conclusion: Effective mitigation through adherence to COLREGs, radar use, routine fouling maintenance, and enhanced safety measures